Cambridge English IELTS 10 with answers : (Cambridge University press, 2017)
Cambridge IELTS 10 provides students with an excellent opportunity to familiarise themselves with IELTS and to practise examination techniques using authentic test material prepared by Cambridge English Language Assessment. It contains four complete tests for Academic module candidates, plus extra Reading and Writing modules for General Training module candidates. An introduction to these different modules is included in each book, together with with an explanation of the scoring system used by Cambridge English Language Assessment. A comprehensive section of answers and tapescripts makes the material ideal for students working partly or entirely on their own.